Drug-induced nephrotoxicity: pathogenic mechanisms, biomarkers and prevention strategies - Wu, Huizi; Huang, Jiaguo (Current drug metabolism, 2018)
Background: Risk factors of drug-induced nephrotoxicity include drug overdose, drug-drug interactions and drug-related adverse effects. Since the usage of some nephrotoxic drugs is still unavoidable in the clinical setting, understanding the pathogenic mechanisms of their nephrotoxicities is critical to decrease the incidence of kidney injury. Early detection of drug-induced nephrotoxicity and reduction of the therapeutic side effects are realistic approaches to avoid the end stage of renal failure. Method: In this review, we summarized the mechanisms and prevention strategies for some drugs that were commonly used clinically and had the possibility of inducing acute and chronic kidney injuries. We discussed the advantages and drawbacks of currently available biomarkers for indicating kidney impairment. In vitro and pre-clinical in vivo models for assessing the nephrotoxicity during the drug developmental stages were also evaluated. Results: Nowadays, an increasing number of biomarkers were discovered for the early diagnosis of kidney injury. In addition, various kinds of in vitro and pre-clinical in vivo models were developed and utilized to minimize the potential nephrotoxicity during the drug development. Conclusion: The discovery of the early biomarkers and development of accurate diagnostic methods are effective prevention strategies for drug-induced kidney impairment.